The Influence of Geographical Conditions on Social, Economic and Environmental Life in Klaces Village, Kampung Laut, Cilacap - Setya, Raudya; Khaq, Muflikhul; Saputri, Mita; Ambarwati, Lina; Suprapto, Yuni (Journal of Edugeography, 2025)
The geographical conditions of an area have a significant influence on the social, economic, and environmental life of the local community. This study aims to analyze the impact of geographical conditions on these aspects in Klaces Village, Kampung Laut District, Cilacap Regency, using qualitative methods. Data were collected through field observations, in-depth interviews with the community and stakeholders, and documentation studies. The results of the study indicate that the geographical conditions of Klaces Village, which are dominated by coastal and swamp areas, cause scattered settlement patterns and limited accessibility, which affect social interaction and access to public services. From an economic perspective, the community relies on the fisheries sector, wetland agriculture, and water transportation as their main sources of livelihood, but limited infrastructure and environmental changes are major challenges in economic sustainability. From an environmental aspect, this village faces problems such as abrasion, tidal flooding, and ecosystem changes that have an impact on the sustainability of natural resources. This study concludes that geographical conditions play an important role in shaping the social, economic, and environmental dynamics in Klaces Village. Therefore, adaptive and sustainable development policies are needed to improve community welfare and maintain ecosystem balance.